Optimasi Jumlah Inokulum dan Laju Aliran terhadap Persentase Penurunan Deterjen, Lipid, Bod Dan Cod pada Sistem Biofilter Kerikil Horizontal - Nur Hidayat; Sri Kumalaningsih; Noor Hamdani; Susinggih Wijana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
The objective of this study was to determine the effect of fl ow rate of waste and the amount of inoculum to improve the quality of wastewater using a horizontal gravel biofi lter. The research was conducted with continuous horizontal gravel biofi lter. Waste materials were derived from the instant noodle soup which had diluted ten times and added with detergent 1.0 g/l. The experimental design used in this research was response surface methodology within two factors: the amount of inoculum and the fl ow rate of waste. Implementation of the biofi lter experiments conducted over 2 months. The results showed that the optimal value obtained were 6.83% inoculum and fl ow rate of 1.44 l/day which resulted in decreasing of BOD to 87.08 %, COD to 85.41%, LAS to 96.22 % and lipid to 81.88 %.ABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh laju aliran limbah dan jumlah inokulum terhadap perbaikan kualitas limbah menggunakan biofi lter kerikil horizontal. Penelitian dilakukan dengan biofi lter kerikil horizontal kontinyu. Bahan limbah diperoleh dari kuah mie instan yang diencerkan sepuluh kali dan ditambah deterjen 1,0 g/l. Rancangan percobaan yang digunakan adalah response surface methodology dengan dua faktor yaitu jumlah inokulum dan laju aliran limbah. Pelaksanaan percobaan dengan biofi lter dilakukan selama 2 bulan. Hasil penelitian menunjukkan bahwa nilai optimal yang diperoleh adalah jumlah inokulum 6,83 % dengan laju aliran 1,44 l/hari yang menghasilkan penurunan BOD sebesar 87,08 %, COD 85,41 %, LAS 96,22 %, dan lipid 81,88 %.